A cluster of mutagenesis revealed an osmotic regulatory role of the OsPIP1 genes in enhancing rice salt tolerance - Leyuan Tao; Bing Wang; Shichao Xin; Wei Li; Shengcai Huang; Laihua Liu; Jing Cui; Qianru Zhang; Xianguo Cheng (Crop Journal, 2023)
Aquaporins play important regulatory roles in improving plant abiotic stress tolerance. To better understand whether the OsPIP1 genes collectively dominate the osmotic regulation in rice under salt stress, a cluster editing of the OsPIP1;1, OsPIP1;2 and OsPIP1;3 genes in rice was performed by CRISPR/Cas9 system. Sequencing showed that two mutants with Cas9-free, line 14 and line 18 were successfully edited. Briefly, line 14 deleted a single C base in both the OsPIP1;1 and OsPIP1;3 genes, and inserted a single T base in the OsPIP1;2 gene, respectively. While line 18 demonstrated an insertion of a single A base in the OsPIP1;1 gene and a single T base in both the OsPIP1;2 and OsPIP1;3 genes, respectively. Multiplex editing of the OsPIP1 genes significantly inhibited photosynthetic rate and accumulation of compatible metabolites, but increased MDA contents and osmotic potentials in the mutants, thus delaying rice growth under salt stress. Functional loss of the OsPIP1 genes obviously suppressed the expressions of the OsPIP1, OsSOS1, OsCIPK24 and OsCBL4 genes, and increased the influxes of Na+ and effluxes of K+/H+ in the roots, thus accumulating more Na+ in rice mutants under salt stress. This study suggests that the OsPIP1 genes are essential modulators collectively contributing to the enhancement of rice salt stress tolerance, and multiplex editing of the OsPIP1 genes provides insight into the osmotic regulation of the PIP genes.